Developing a contracts law keyword list (CLKL) for academic legal education: A corpus-based, keyness-informed study - Abdullah Alasmary (PLoS ONE, 2026)
This study introduces the Contracts Law Keyword List (CLKL), a discipline-specific, genre-focused resource of pedagogically useful lexical items in contract law, an understudied legal subfield at the nexus of law and commerce. Items in the CLKL are drawn from authentic language data using predetermined frequency, range, and keyness parameters. The CLKL includes 747 keywords (KWs) typical of written contract law textbooks, covering 4.22% of all words in the study corpus and 4.19% in the law section of the British National Corpus (BNC). Structural analysis revealed the pervasive presence of nouns, which account for nearly half of all grammatical categories. Adjectives and verbs constitute the second- and third-largest groups of KWs. There are rare instances of adverbs, archaic terms, prepositions, and words with dual structural functions. These findings underscore the importance of creating a field-specific vocabulary list that can address the lexical demands of a growing number of law students and international practitioners. The CLKL may also be used to deepen knowledge of domain-specific vocabulary, enhance engagement with authentic language examples, and foster awareness of expert-authorized conventions typical of legal contracts. Law educators can draw on the list while designing instructional materials or planning classroom activities.